School-aged Schistosoma mansoni infection levels after long-term programmatic control show failure to meet control programme targets and evidence of a persistent hotspot: evaluation of the FibroScHot trial baseline data. - Fred Besigye; Candia Rowel; Moses Adriko; Fredrick J Muyodi; John Joseph Kisakye; Rosemary Nalwanga; Birgitte J Vennervald; Fred Nuwaha; Edridah M Tukahebwa; Shona Wilson (PLoS Neglected Tropical Diseases)
Background Treatment guidelines for schistosomiasis recommend increasing frequency of preventative chemotherapy (PC) administration of praziquantel to twice per annum in persistent hotspots of transmission, in combination with integrated control strategies. FibroScHot was an individual randomised superiority trial designed to examine twice per annum and four times per annum treatment frequency. It was conducted in two primary schools, Buhirigi and Kaiso, in Hoima District Uganda - a designated Schistosoma mansoni high transmission area in which PC is targeted at children and adults. The baseline parasitology data was assessed against international control programme thresholds of success and the criteria for persistent hotspots. Further, the study also assessed the potential for integrated control strategies within the surrounding communities. Methodology/principal findings The prevalence of infection, heavy infection and the infection intensity were derived for 700 participants from Kato-Katz examination of one stool sample. Neither school met the threshold of morbidity control (<5% with heavy infection). A strong school effect was observed in models of prevalence and prevalence of heavy infection, with these being greater in Kaiso. By prevalence, Kaiso was a high transmission area and Buhirigi a moderate transmission area. Kaiso but not Buhirigi met the definition of a persistent hotspot. Persistent hotspot classification did not change when intensity of infection was used. Intermediate snail hosts were collected at both Kaiso landing site and from the River Hoimo in Buhirigi, though in smaller numbers in the latter. Questionnaire data indicates that reliance on water collection from transmission sites and open defecation occurs more frequently in Kaiso than in Buhirigi. Conclusions The criteria for persistent hotspots were met in the high transmission but not the moderate transmission community despite neither community meeting the threshold of morbidity control. This disconnect indicates that endemic communities exist in which control has not been achieved but increased frequency of treatment is currently not recommended. FibroScHot will be able to inform on whether widening the current recommendation of increased treatment frequency to these communities will achieve improved control. Evidence provided also indicates scope for the integrated control strategies of vector control and WASH improvements in both the participating communities.